Compositional features, microbial quality, and sensory evaluation of milk and cheese obtained from Oases autochthonous Arbi goat - Mounir Nafti; Zahran Khaldi; Mohamed Amine Ferchichi; Safa Bejaoui; Mohamed Tabarek Jilani; Bayrem Jemmali (Journal of Agriculture and Environment for International Development)
The purpose of this study was to assess the compositional features and microbiological quality of the milk produced by the autochthonous oasis goat in order to evaluate its suitability for cheesemaking. To attain this, two fresh cheeses with and without basil flavor were prepared and evaluated. One hundred milk samples were collected from multiparous lactating Arbi goats reared in the continental oasis region of Tunisia and processed into unflavored and basil-flavored cheese according to a traditional recipe. Milk samples were subjected to physical, chemical, and microbial analyses. The basic composition, mineral content, and bacterial profile of the cheeses were determined. In addition, the cheeses were subjected to organoleptic evaluation. The physical parameters of the analyzed milk were 6.54, 15.64, and 1030.89 for pH, acidity, and density, respectively. For the chemical properties of the milk, the results showed a respectable level of nutritional quality with a noteworthy content of dry matter, fat, protein, casein, and minerals, especially potassium, calcium, and phosphorous. With an average yield of 25%, the assessment of both cheeses illustrated good hygienic quality for all microflora examined, except total coliforms; a very noticeable organoleptic quality, as judged by all jury members; and satisfactory nutritional quality, with a significant protein and lipid level and a richness of mineral elements, particularly high levels of calcium and phosphorus. Basil-flavored cheese had the best aroma and taste, making it highly desirable to consumers. With the exception of coliforms and E. coli, the products bacteriological quality was acceptable and met legal requirements. The total absence of dangerous Salmonella and sulfite-reducing Clostridium strictly met the legal standards. The findings revealed the substantial chemical and nutritional value of milk and cheese made from local goats. However, additional studies are required to improve the microbial quality of the studied products.